Russian identities a historical survey - Riasanovsky, Nicholas V. (Nicholas Valentine), 1923-2011 (Oxford University Press, 2005)
Nicholas Riasanovsky investigates the question of Russian identity, looking at changes and continues over a huge territory, many centuries, and a variety of political, social and economic structures.